Theoretical study of micro/nano roughness effect on water-solid triboelectrification with experimental approach. (October 2018) - Lee, Jeong-Won; Hwang, Woonbong
Abstract: The application of micro and nano surface roughness in solid-solid contact electrification based triboelectric nanogenerators (TENGs) has been a widely accepted method for pursuing higher energy output. However, the roughness enhancement needs to be reconsidered in the case of TENGs based on water-solid contact electrification because water-solid contact has clearly different interfacial behavior from solid-solid contact. This study reports a theory for investigating the effect of micro/nano roughness on water-solid contact electrification. The relation between micro/nano roughened surface and water-solid contact electrification is developed and specified by utilizing wetting and rheological properties such as fraction of the area in contact and thickness of the air gap layer. For the fabrication of water-driven TENG (WTENG), aluminum plates are anodized and fluorinated to form the dielectric layer and triboelectric layer, respectively. Three types of surface roughness were fabricated by adjusting the fabrication conditions. The WTENG with the lowest roughness shows approximately 14 times higher current and 9 times higher voltage than the WTENGs with higher roughness. The theoretical equations for water-solid contact electrification correspond well with the experimental results with high accuracy. The theory derived in this work is the first insightful perspective on roughness related liquid-solid electrification. Graphical abstract: fx1 Highlights: A precise theoretical model for water-solid triboelectrification was established. Water driven triboelectric nanogenerators with various roughness were fabricated. The experimental results well corresponded with theoretical calculation.